The Influence of Using the PWIM Strategy on the Guided Writing Ability of Grade VII Students in Arabic Language Learning - Nisa, Khilwatun; Ghufron, Zaki; Indriana, Dina; Ubaidillah, Ubaidillah (AS-SABIQUN, 2025)
This study was conducted because of the low ability of students in writing skills (kitabah) in class VII of SMP Boarding School Daarul Barkah.Thus this study aims to obtain information about the effect of using the picture word inductive model (PWIM) strategy applied to Arabic language subjects, especially in writing learning, namely kitabah al-muwajjahah. The research methodology used is quantitative with quasi experiment with nonequivalent control group design. This study used two classes as research samples, namely class VII a as a control class with 15 students and class VII b as an experimental class, which numbered 16 students, with a total of 31 students. The sample used in this study used random sampling technique which was carried out randomly in the experimental class. The experimental results obtained and have been processed in the paired sample t-test show (sig < a) which is (.000 < 0.05) stating H⁰ is rejected, and Hª is accepted, indicating that student learning outcomes regarding kitabah skills using the PWIM strategy are higher than student learning outcomes using conventional learning. The conclusion of this study is that the PWIM strategy applied to Arabic language learning, especially for learning kitabah al-muwajjah, has a significant effect seen from the increase in post-test scores after the use of the PWIM strategy.